The experience of treatment of newborns with artificial intestinal fistulas - O. Losev; I. Dilanyan; N. Sivolap; D. Samofalov; A. Kossey; I. Belesto; N. Gavrilishen; Yu. Kachkovskiy; B. Gorelick (Bukovynian State Medical University, 2013)
The most often complications of intestinal stomas, methods of their prophylaxis and treatment was generalized according to results of analyses of treatment of 92 newborns with intestinal stomas in Odessa.